The stance of the European Union and the United Nations towards the Arab Spring - Λιάτσα, Φωτεινή (Πανεπιστήμιο Πελοποννήσου, 2016)
The Southern Mediterranean neighborhood has always been an important driver in the formulation of policies, both in European and global level, since in the eyes of the international community it was a barrier providing protection to the developed and peaceful West from the Middle East conflicts and the least developed Africa. Nevertheless, the Arab Spring that started on December 2010 caught the international community off guard, including international organizations such as the European Union (EU) and the United Nations (UN), which had –in a very short time frame- to elaborate new policies and establish new instruments in order to tackle its repercussions and contribute to the stability in the region. In the present thesis we briefly present the development of the Arab Spring in each country involved and then we examine the response of the two aforementioned organizations and their actions regarding the Arab Spring phenomenon. The Organizations are assessed based on their actions and the decisions made but also taking into consideration the framework in which they operated. The conclusion is that both international organizations under examination failed to demonstrate the will that was necessary during the first year of the Arab Spring in order to avert the deterioration of the situation in the countries involved, a situation that is still unfolding in a very disturbing way six years after the outbreak of the revolution.
Η στάση της Ευρωπαϊκής Ένωσης και του Οργανισμού Ηνωμένων Εθνών απέναντι στην Αραβική Άνοιξη
Keywords: Οργανισμός Ηνωμένων Εθνών; Ευρωπαϊκή Ένωση, Χώρες της--Εξωτερικές σχέσεις; Αραβική Άνοιξη; Ανθρώπινα δικαιώματα; Αραβική Άνοιξη; Ευρωπαϊκή Ένωση; ΝΑΤΟ; Ενέργειες; Στρατιωτική επέμβαση